2016
DOI: 10.1371/journal.pone.0162103
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Analysis of F1 Hybrids between Genetically Modified Brassica napus and B. rapa

Abstract: A number of studies have been conducted on hybridization between transgenic Brassica napus and B. rapa or backcross of F1 hybrid to their parents. However, trait changes must be analyzed to evaluate hybrid sustainability in nature. In the present study, B. rapa and transgenic (BrAGL20) B. napus were hybridized to verify the early flowering phenomenon of F1 hybrids, and F1 hybrid traits were analyzed to predict their impact on sustainability. Flowering of F1 hybrid has been induced slightly later than that of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…This study explored the morphological and molecular characteristics that can be utilized to identify the occurrence of introgression from B. napus to B. rapa varieties in Taiwan. It has been reported that triploid F 1 hybrids with the AAC genome (2n = 29) could be produced by interspecific hybridization from B. napus to B. rapa (Luijten et al 2015;Sohn et al 2016). However, the morphological characteristics and genetic relationships of B. napus, B. rapa, and their hybrid progenies remain unclear in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…This study explored the morphological and molecular characteristics that can be utilized to identify the occurrence of introgression from B. napus to B. rapa varieties in Taiwan. It has been reported that triploid F 1 hybrids with the AAC genome (2n = 29) could be produced by interspecific hybridization from B. napus to B. rapa (Luijten et al 2015;Sohn et al 2016). However, the morphological characteristics and genetic relationships of B. napus, B. rapa, and their hybrid progenies remain unclear in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…GM B. napus (Youngsan) seeds with CAMV 35S-regulated bar gene and an early flowering gene ( BrAGL20 ) were kindly provided by Yeon-Hee Lee, National Institute of Agricultural Sciences, Jeonju, Korea. For hybrid preparation, artificial hand pollination was done with B. rapa and GM B. napus and the seeds of F1 hybrids ( B. rapa X GM B. napus ) were used for further studies [ 8 ]. The hybrids were confirmed through a survival assay after 0.3% Bastar treatment, the phenotype of the hybrids, and polymerase chain reaction with partial 35S promoter and BrAGL20 [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…For hybrid preparation, artificial hand pollination was done with B. rapa and GM B. napus and the seeds of F1 hybrids ( B. rapa X GM B. napus ) were used for further studies [ 8 ]. The hybrids were confirmed through a survival assay after 0.3% Bastar treatment, the phenotype of the hybrids, and polymerase chain reaction with partial 35S promoter and BrAGL20 [ 8 ]. All the plants were grown in soil cups ( Figure 6 ) and maintained in a controlled environment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations